Protein Quantitative Trait Loci Analysis Identifies Genetic Variation in the Innate Immune Regulator TOLLIP in Post–Lung Transplant Primary Graft Dysfunction Risk. Issue 3 (10th December 2015) - Cantu, E.; Suzuki, Y.; Diamond, J. M.; Ellis, J.; Tiwari, J.; Beduhn, B.; Nellen, J. R.; Shah, R.; Meyer, N. J.; Lederer, D. J.; Kawut, S. M.; Palmer, S. M.; et al.
Abstract: The authors previously identified plasma plasminogen activator inhibitor‐1 (PAI‐1) level as a quantitative lung injury biomarker in primary graft dysfunction (PGD). They hypothesized that plasma levels of PAI‐1 used as a quantitative trait could facilitate discovery of genetic loci important in PGD pathogenesis. A two‐stage cohort study was performed. In stage 1, they tested associations of loci with PAI‐1 plasma level using linear modeling. Genotyping was performed using the Illumina CVD Bead Chip v2. Loci meeting a p < 5 × 10 −4 cutoff were carried forward and tested in stage 2 for association with PGD. Two hundred ninety‐seven enrollees were evaluated in stage 1. Six loci, associated with PAI‐1, were carried forward to stage 2 and evaluated in 728 patients. rs3168046 (Toll interacting protein [ TOLLIP ]) was significantly associated with PGD (p = 0.006). The increased risk of PGD for carrying at least one copy of this variant was 11.7% (95% confidence interval 4.9–18.5%). The false‐positive rate for individuals with this genotype who did not have PGD was 6.1%. Variants in the TOLLIP gene are associated with higher circulating PAI‐1 plasma levels and validate for association with clinical PGD. A protein quantitative trait analysis for PGD risk prioritizes genetic variations in TOLLIP and supports a role for Toll‐like receptors in PGD pathogenesis. Abstract : Plasma plasminogen activator inhibitor‐1 quantitative trait analysis prioritizes genetic variations in TOLLIP for posttransplant primary graft dysfunction and supports a role for Toll‐like receptors in primary graft dysfunction pathogenesis.